Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1097/01.opx.0000171817.32551.05
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Eye Color and Corneal Sensitivity Measured Using a Belmonte Esthesiometer

Abstract: We were generally unable to demonstrate the relationship between eye color and sensitivity reported previously using a Cochet-Bonnet esthesiometer. However, for a subset of subjects with palest irises, there appears to be a linear association between eye color and sensitivity to cooling stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
1
7
1
Order By: Relevance
“…Studies have reported both qualitative and quantitative evidence of increased startle magnitude among high BI infants and children (Barker et al 2014), as well as higher BI scores among children with blue vs. brown eye color (Rosenberg & Kagan 1989). Blue-eyed adults have also been reported to have higher reactivity and lower detection thresholds in response to a range of diferent sensory stimuli (Hood et al 1976; Herbener et al 1989; Barrenas & Hellstrom, 1996; Henderson et al 2005; Acosta et al 2006). In the present sample, eye color was recorded for 261 subjects, blind to hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported both qualitative and quantitative evidence of increased startle magnitude among high BI infants and children (Barker et al 2014), as well as higher BI scores among children with blue vs. brown eye color (Rosenberg & Kagan 1989). Blue-eyed adults have also been reported to have higher reactivity and lower detection thresholds in response to a range of diferent sensory stimuli (Hood et al 1976; Herbener et al 1989; Barrenas & Hellstrom, 1996; Henderson et al 2005; Acosta et al 2006). In the present sample, eye color was recorded for 261 subjects, blind to hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…Corneal sensitivity provides an important measure of corneal nerve function. Stimulation is conveyed via the trigeminal nerve via three different sensory receptors: mechanical (mechano‐nociceptors), chemical (polymodal nociceptors) and thermal (cold receptors) 28,31 . The mechanical receptors are myelinated fibres and constitute approximately 20 per cent of corneal sensory fibres.…”
Section: Corneal Innervation and Morphologymentioning
confidence: 99%
“…Millodot[ 7 ] and Roszkowska et al,[ 9 ] using the contact Cochet–Bonnet esthesiometer, did not find a significant difference in corneal sensitivity between men and women. Henderson et al[ 8 ] also found the same result using a non-contact corneal esthesiometer. On the other hand, Golebiowski et al[ 10 ] and Acosta et al[ 12 ] using non-contact corneal esthesiometry reported that corneal sensitivity in women is higher than men.…”
Section: Discussionmentioning
confidence: 59%
“…The issue of gender differences in corneal sensitivity has been much disputed in the field of neuro-ophthalmology. In a number of previous studies,[ 7 8 9 ] no difference was found between the genders; however, in Golebiowski's study,[ 10 ] men showed higher thresholds, i.e., less corneal sensitivity, than women. The aim of this study was to measure and compare corneal sensitivity between men and women.…”
Section: Introductionmentioning
confidence: 77%